An objective assessment of botulinum toxin type A injection in the treatment of post-facial palsy synkinesis and hyperkinesis using the synkinesis assessment questionnaire. Issue 11 (November 2017) - Neville, Catriona; Venables, Vanessa; Aslet, Margaret; Nduka, Charles; Kannan, Ruben
Summary: This study aimed to provide reliable and valid evidence that botulinum toxin type A (BTX-A) is a successful treatment for facial synkinesis in facial palsy by using the synkinesis assessment questionnaire (SAQ) tool. Fifty-one patients completed questionnaires pre- and post-BTX-A treatment over 103 cycles of treatment. Each patient was individually assessed and then treated according to their presenting symptoms with a dosage in each injection site of between 0.5 and 5 U of BTX-A. A two-tailed paired samples t-test was used to compare the scores for each question before and after treatment. A significant difference was found between all scores before and after treatment at the level of p < 0.05. There was not only an improvement in the mean score in the post-treatment group but also a smaller spread of scores in the post-treatment group than in the pre-treatment group. The study showed that SAQ scores decreased significantly for every question on the SAQ after treatment. This indicates that BTX-A is an effective treatment for synkinesis, adding further weight to current evidence. The study also indicated that BTX-A continues to be effective even after three rounds of treatment, with a significant decrease in overall scores after each treatment cycle.